Students' Speaking Anxiety in EFL Classroom - Asysyfa Asysyfa; Ayu Maulidia Handyani; Siska Rizkiani (PROJECT (Professional Journal of English Education), 2019)
This study investigated the students’ speaking anxiety in the first grade of vocational high school. It emphasized on the level, the causal factors and the strategy to reduce the anxiety. It applied descriptive qualitative to answer the research questions. The data were obtained through questionnaire and interview. The Foreign Language Classroom Anxiety Scale (FLCAS) questionnaires and interview were administered to 30 students. It was revealed that [a1] the factors that make students feel anxious in speaking in English were lack of preparation, afraid of left behind in understanding the material or what the teacher talks about, afraid of making mistakes, afraid of being laughed by his/her friends, unconfident to spell, pronounce and select the words in English. It was also found that there were eight students in level Relaxed, twelve students in level Mildly Anxious, and ten students in level Anxious. Last, the strategies that students should do to reduce their anxiety are do more preparation before speaking, try to be more confident in saying English words, and pronunciation practice. Keywords:   Speaking, Speaking anxiety, EFL Classroom. [a1]It was revealed that